Characterization of edible soldier fly protein and hydrolysate altered by multiple-frequency ultrasound: Structural, physical, and functional attributes. (August 2020) - Mintah, Benjamin Kumah; He, Ronghai; Dabbour, Mokhtar; Xiang, Jiahui; Jiang, Hui; Agyekum, Akwasi A.; Ma, Haile
Graphical abstract: Highlights: Sonication did not cause change in lightness of protein hydrolysates. Zeta, dispersibility, and thiol value(s) increased following sonication. Turbidity, and particle size (of samples) decreased after sonication. SDS-PAGE profile showed similar bands for control and sonicated samples. Ultrasonic-treated hydrolysates exhibited high fraction of small-sized peptides. Abstract: The effect of conventional (control), and different ultrasonic treatment modes (fixed, and sweep frequency ultrasound) on structural, physical and functional traits of soldier fly ( Hermetia illucens ) larvae protein preparations and hydrolysates were examined. Ultrasonication significantly increased lightness ( L* ) of protein isolates by x ¯ 7.46 % compared to control. Sonic-treated (particularly sweep-type) isolates and hydrolysates showed significant increases in thiol value, reconstitutability function (pH 2–10), and surface charge; and significant decreases in turbidity, and particle size, relative to controls. Protein isolates were characterized by higher molecular weight ( M W ) using SDS-PAGE, whereas hydrolysates were lower (with no observable variances). By numerical estimation, hydrolysates (especially the sweep-treated) showed significantly lower M W (<1000 Da). Deconvoluted FTIR spectra (α-helix, β–sheet/turn, random coil fractions), and UV spectra analyses showed differences in samples. Treatment type (sweep/ fixed frequency ultrasound) could be used to alter protein structure, modify functionality, and thereby usage of H. illucens protein/hydrolysate preparations.